PRESENCE OF ALBUMIN IN ERYTHROCYTE LYSATE OF AUTOIMMUNE HAEMOLYTIC ANAEMIA PATIENTS OBSERVED IN ELECTROPHORETOGRAM - John, Mathew; Maria, Evelyn; Merin Sabu, Minu; Asok, Karthika; R, Sinju (Journal of Biomedical and Pharmaceutical Research, 2019)
Autoimmune haemolytic anaemia is a condition in which autoantibodies present against self erythrocytes which leads to severe haemolysis and loss of haemoglobin. In the present study we compared the electrophoretic band patterns between control and autoimmune haemolytic anaemia and non autoimmune iron deficiency anaemia erythrocyte lysate samples. We observed the presence of a band which was specific to autoimmune haemolytic erythrocyte lysates in the region of 70 Kd which was later identified as albumin and was distinctly absent in control as well as iron deficiency non autoimmune haemolytic samples. In addition, we have noticed that the catalase in the region of 60 Kd was found to be decreased in its band intensity in haemolytic anaemia samples compared to control. The presence of both albumin and catalase in the respective positions in the electrophoretic gel was confirmed by in gel trypsin digestion followed by mass spectrometry. The other erythrocyte proteins visible in the region of 25 Kd were found to have an overall decrease in band intensity in haemolytic anaemia samples compared to control. The specific presence of albumin in autoimmune haemolytic erythrocyte lysate is the main highlight of the work which was not reported till date and further studies could reveal the exact role of albumin in autoimmune haemolytic conditions.Key words: Autoimmune haemolytic anaemia, erythrocytes, electrophoresis, albumin, catalase